2014
DOI: 10.1016/j.febslet.2014.04.032
|View full text |Cite
|
Sign up to set email alerts
|

Membrane rigidification functions upstream of the MEKK1‐MKK2‐MPK4 cascade during cold acclimation in Arabidopsis thaliana

Abstract: a b s t r a c tThe MEKK1-MKK2-MPK4 cascade is activated during cold acclimation. However, little is known regarding the perception of low temperature. In this study, we demonstrate that treatment of Arabidopsis with a membrane rigidifier, DMSO, caused MPK4 activation concomitantly with MEKK1 and MKK2 phosphorylation, as well as the cold-inducible gene COR15a expression. These processes are similar to the effects of cold treatment, whereas benzyl alcohol (BA), a membrane fluidizer, prevented such cold-induced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 22 publications
(35 reference statements)
2
58
0
Order By: Relevance
“…This would then activate a specific mitogen-activated protein kinase kinase kinase (MEKK1) that then targets protein kinase kinase2 (MKK2; Furuya et al, 2013). This pathway leads to gene activation and freezing tolerance (Furuya et al, 2014). [Ca 2+ ] cyt elevation would also activate CIPK3, that acts an intersect with ABA signaling (Kim et al, 2003).…”
Section: Mechanical Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…This would then activate a specific mitogen-activated protein kinase kinase kinase (MEKK1) that then targets protein kinase kinase2 (MKK2; Furuya et al, 2013). This pathway leads to gene activation and freezing tolerance (Furuya et al, 2014). [Ca 2+ ] cyt elevation would also activate CIPK3, that acts an intersect with ABA signaling (Kim et al, 2003).…”
Section: Mechanical Stressmentioning
confidence: 99%
“…Work on M. sativa suspension cells showed that increasing membrane fluidity at 4°C prevented the Ca 2+ influx across the PM that is necessary to trigger gene expression for freezing tolerance (Orvar et al, 2000). Conversely, imposing membrane rigidity at normal temperature triggers activation of the Ca 2+ -dependent MEKK1-MKK2-MPK4 pathway in Arabidopsis seedlings (Furuya et al, 2014). The possibility that mechanosensitive channels are involved in cold-induced [Ca 2+ ] cyt signaling merits investigation.…”
Section: Mechanical Stressmentioning
confidence: 99%
“…Confronted with these disruption, some plants have the ability to adapt through cellular regulatory mechanisms based on protein synthesis2, membrane composition changes34, and activation of active oxygen scavenging systems5. These adaptive mechanisms rely in part on gene induction6 and protein modifications7.…”
mentioning
confidence: 99%
“…The results of these two studies reveal that during cold exposure some proteins are phosphorylated by protein kinases, whereas others are dephosphorylated by protein phosphatases. Presently, many different kinases or phosphatases under cold stress had been identified, such as Calcium dependent protein kinases (CDPK)16, Ca 2+ /calmodulin-dependent protein kinases (CAMK)17, MAPK (mitogen activated protein kinase) module718, STY kinases19, CBL-interacting protein kinase (CIPK)2021, OST122 and AP2C1 proteins23. Phosphorylation changes of MAPK cascades in plant cold resistance have been well reported, particularly in model plants.…”
mentioning
confidence: 99%
“…AtMKK2 is activated during cold signalling and phosphorylates AtMPK4/6 (Teige et al 2004), and membrane rigidification occurs upstream of the MEKK1-MKK2-MPK4 cascade during cold acclimation (Furuya et al 2014). Furthermore, NtMEK2 phosphorylates NtSIPK/WIPK, MsSIMKK interacts with and phosphorylates MsSIMK, and OsMKK4/5 phosphorylates OsMPK3/6 (Kong et al 2011).…”
Section: Discussionmentioning
confidence: 99%